An optical fiber loop sensor for vibration monitoring - Domański, Andrzej Witold; Poczęsny, Tomasz; Prokopczuk, Krzysztof; Makowski, Piotr (Photonics Letters of Poland, 2010)
In harmful environments such as refineries and factories, with a strong electromagnetic field, fire hazard and explosion risk there is a need to monitor the vibration of equipment and industrial infrastructure. Applying traditional measurement methods is a significant difficulty because of electric current which creates the risk of fire and influence of electromagnetic noise on these electronic devices. The solution to this problem is optical fiber measuring and monitoring methods. In this paper we present an optical sensor based on a fiber loop which can monitor vibrations and measure small relative displacements. Full Text: PDF References T.R. Woliński, D. Budaszewski, A.W. Domański, S. Ertman, G.Goleniewski, M. Wydmański, "Optical fiber rotation sensor for application in oil refinery and high electromagnetic noise environment", Proc. SPIE 6616, 66161U (2007).[CrossRef] T.R. Woliński, A.W. Domański, D. Budaszewski, S. Ertman, "Multiparameter modular optical fiber sensor for applications in oil refinery", Proc.SPIE 6585, 65850H (2007).[CrossRef] G. Rajan,Y. Semenova, G. Farrell, "All-fibre temperature sensor based on macro-bend singlemode fibre loop", Electr. Lett. 44, 1123 (2008).[CrossRef] D. Marcuse, "Curvature loss formula for optical fibers", J. Opt. Soc. Am. B 66, 216 (1976).[CrossRef] R.T. Schermer, J.H. Cole, "Improved Bend Loss Formula Verified for Optical Fiber by Simulation and Experiment", IEEE J. Quantum Elect 43(10), Oct (2007). P. Wang, Q. Wang, G. Farrell, G. Rajan, T. Freir, J. Cassidy,"Investigation of macrobending losses of standard single mode fiber with small bend radii", Microwave and Opt. Techn. Lett. 49(9), 2133 (2007).[CrossRef]